1996
DOI: 10.1021/ic960661q
|View full text |Cite
|
Sign up to set email alerts
|

Host−Guest Interactions of Inorganic Phosphates with the Copper(II) Complexes of the Hexaaza Macrocyclic Ligand 3,6,9,17,20,23-Hexaazatricyclo[23.3.1.111,15]triaconta-1(29),11(30),12,14,25,27-hexaene

Abstract: The host-guest interactions between ortho-, pyro-, and tripolyphosphate anions and the mono and dinuclear copper(II) complexes of the hexaaza macrocyclic ligand BMXD (3,6,9,17,20,23-hexaazatricyclo[23.3.1.1(11,15)]triaconta-1(29),11(30),12,14,25,27-hexaene) were investigated by potentiometric equilibrium methods. Ternary complexes are formed in aqueous solution as a result of coordinate bonding, hydrogen bond formation, and Coulombic attraction between the host and guest. Formation constants for all the specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…559 In addition, direct competition experiments led to the conclusion that the dinuclear complex 509:Cu 2 interacts more favorably with pyrophosphate than it does with monophosphate near neutral pH. A slight selectivity for triphosphate over pyrophosphate by this complex was also found under these conditions.…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 97%
“…559 In addition, direct competition experiments led to the conclusion that the dinuclear complex 509:Cu 2 interacts more favorably with pyrophosphate than it does with monophosphate near neutral pH. A slight selectivity for triphosphate over pyrophosphate by this complex was also found under these conditions.…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 97%
“…We have now chosen as a receptor the dicopper( II ) complex of the bisdiene macrocycle 3,6,9,16,19,22‐hexaazatricyclo[22.2.2.2(11.14)]triaconta‐1(26),11(12),13,24,27, 29‐hexaene ( L ). We expected that, in view of the coordinative unsaturation of the two metal centers and the correct Cu II ⋅⋅⋅Cu II distance, the dinuclear complex of L , [Cu${{{\rm II}\hfill \atop 2\hfill}}$ ( L )] 4+ ( R ), could be a reasonably good candidate for behaving as a fluorescent CE for PPi 11…”
Section: Ki Values For the Equilibrium: R + I⇌[ri] At Phmentioning
confidence: 99%
“…Recently, it was reported that the binuclear complexes of the title compound, (I), and its analogues can accelerate the hydrolysis of bis(p-nitrophenyl)phosphate and adenosine triphosphate (Ragunathan & Schneider, 1996;Lu et al, 1998). On the other hand, these compounds and their metal complexes are good receptors for inorganic phosphates and ribonucleic acid (Nation et al, 1996;Li et al, 1997). Therefore, the structure of the title compound may prove useful both for understanding the mechanisms of hydrolysis and for the design of new compounds.…”
Section: Commentmentioning
confidence: 99%